Perancangan Website Video Streaming Dengan Memanfaatkan Algoritma Rice Codes Dalam Memaksimalkan Space Penyimpanan Server - Wiyuda Pratama Mahardika (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The website is currently growing rapidly, now there is more that users can do on the website, not only to search for information or exchange information. Currently the function of the website has developed much better, even now the website can be used as a video streaming service where users can view the videos they like on the website. However, the size of the video that is large enough can be a barrier or a cause of increasing the cost of using storage on the server. Because the larger the size of the uploaded video, the more storage the server will need to store the video. Compression is a technique that can be used to reduce the size of a data by removing the number of bits contained in a file. For this reason, in dealing with relatively large video file sizes, this solution can be used to overcome this problem. The rice codes algorithm is one of the compression algorithms that can be used to reduce the size of data and is quite effective in compressing video files. In its implementation, utilizing compression techniques using the rice codes algorithm in compressing video files is considered very effective because it can produce a compression ratio (CR) value of 56.875%. Of course, with the results obtained, video files that are relatively large in size can be reduced by half from their original size.